Upaya Peningkatan Pengetahuan dan Sikap Siswa SMP dalam Pencegahan Penggunaan NAPZA - Sumbung, Heryanto; Martha, Evi (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2020)
Background: Ransiki is a district in South Manokwari Regency which was a new division in West Papua Province. Junior high school students in Ransiki are at risk of drug use. An effort should be made to improve the knowledge and attitude of junior high school students as a form of prevention of drug use. This study aimed to improve knowledge and attitude for the prevention of drug use in junior high school students in Ransiki using the training module